A school-based intervention to promote physical activity among adolescent girls: Rationale, design, and baseline data from the Girls in Sport group randomised controlled trial - Puglisi Lauren; Morgan Philip J; Lubans David R; Cotton Wayne G; Okely Anthony D; Miller Judy; Wright Jan; Batterham Marijka J; Peralta Louisa R; Perry Janine (BMC, 2011)
Abstract Background Physical activity levels decline markedly among girls during adolescence. School-based interventions that are multi-component in nature, simultaneously targeting curricular, school environment and policy, and community links, are a promising approach for promoting physical activity. This report describes the rationale, design and baseline data from the Girls in Sport group randomised trial, which aims to prevent the decline in moderate-to-vigorous intensity physical activity (MVPA) among adolescent girls. Methods/Design A community-based participatory research approach and action learning framework are used with measurements at baseline and 18-month follow-up. Within each intervention school, a committee develops an action plan aimed at meeting the primary objective (preventing the decline in accelerometer-derived MVPA). Academic partners and the State Department of Education and Training act as critical friends. Control schools continue with their usual school programming. 24 schools were matched then randomized into intervention (n = 12) and control (n = 12) groups. A total of 1518 girls (771 intervention and 747 control) completed baseline assessments (86% response rate). Useable accelerometer data (≥10 hrs/day on at least 3 days) were obtained from 79% of this sample (n = 1199). Randomisation resulted in no differences between intervention and control groups on any of the outcomes. The mean age (SE) of the sample was 13.6 (± 0.02) years and they spent less than 5% of their waking hours in MVPA (4.85 ± 0.06). Discussion Girls in Sport will test the effectiveness of schools working towards the same goal, but developing individual, targeted interventions that bring about changes in curriculum, school environment and policy, and community links. By using community-based participatory research and an action learning framework in a secondary school setting, it aims to add to the body of literature on effective school-based interventions through promoting and sustaining increased physical activity participation among adolescent girls. Trial Registration Number Australia and New Zealand Clinical Trials Register (ANZCTR): ACTRN12610001077055